PENINGKATAN PENGETAHUAN IBU HAMIL TERHADAP KEHAMILAN RESIKO TINGGI - Deby Meitia Sandy (Khidmah, 2022)
A high risk pregnancy is a pregnancy that will cause greater danger and complications to both the mother and the fetus to be conceived during pregnancy, childbirth or the postpartum period. More than 90% of maternal deaths are caused by obstetric complications during pregnancy, childbirth and the puerperium. The causes of maternal death are bleeding, hypertension, infection, circulatory system disorders, and metabolic disorders. The purpose of this activity is to increase the knowledge of pregnant women about high risk pregnancies in the "X" Midwife Independent Practice. The method in this community service is discourse and question and answer by giving leaftet which was attended by 23 participants. The results of this activity there is an increase in knowledge of pregnant women in knowing high risk pregnancies with very enthusiastic participants in asking questions and the results of the evaluation obtained an increase in knowledge ftrom post test results. The conclusion of this activity is that there is an increase in the knowledge of pregnant women in knowing high risk pregnancies that can harm the mother and fetus so that pregnant women can detect early and avoid high risk pregnancies to themselves and their environment.